UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN SURUHAN (Peperomia pellucida L. Kunth) TERHADAP Propionibacterium acnes PENYEBAB JERAWAT - Yufiradani, Yufiradani; Mayefis, Delladari; Marliza, Hesti (Jurnal Riset Kefarmasian Indonesia, 2020)
Acne is one of the most common skin diseases that occur at all ages, especially in adolescents who are just experiencing puberty. One of the plants that has antibacterial properties is the leaves of suruhan. However untill now not found research of suruhan leaf used as an acne medicine. The aim of this study was to determine the antibacterial activity of suruhan leaf extracts on the growth of Propionibacterium acnes. The method used is disc diffusion by given 5 treatments starting with a concentration of 15%, 20%, 25%, positive control of clindamycin and negative control of aquadest.. The results obtained from leaf extracts were able to inhibit the growth of P. acnes bacteria in various concentrations. Suruhan leaf extracts at a concentration of 25% showed response resistance was greater than other concentrations. The one way Anova SPSS test showed p <0.05 which means that there were differences in the inhibitory concentration of various extracts on the growth of P. acnes that cause acne